Exploring the legal means of enhancing access to essential medicines in South Africa - Moyo, Admark (Centre for Law and Society, 2025)
The introduction of ARVs to the care and treatment of HIV and AIDS must comply with South African patent law and international obligations under the TRIPS agreement. However, the prices of patented and/or branded drugs supplied by the manufacturers may prevent equitable access to necessary drugs for South Africans. Recent international trade agreements and the South African law provide a number of ways to address this dilemma. Therefore, if it is deemed necessary and expedient, the government may consider the implementation of measures such as voluntary licensing, compulsory licensing and parallel importation to purchase drugs at affordable and favourable prices (my emphasis).